Magnet ingestion leading to intestinal fistulae, phytobezoar formation, and small bowel obstruction - Kendall M. Lawrence; Matthew Iyer; Prerana Baranwal; Aliza Solomon; Nitsana A. Spigland (Elsevier, 2019)
Ingestion of neodymium magnets carries risks of dangerous intestinal complications including necrosis of the intestinal wall, bowel perforation, enteroenteric fistulae, and even death. Prompt endoscopic or surgical removal can prevent these complications. Here we report a case of unwitnessed ingestion of 19 neodymium magnets that went unrecognized for two weeks before presenting with small bowel obstruction due to a phytobezoar and numerous gastrojejunal and jejunojejunal fistulae. The child underwent a challenging laparotomy, lysis of adhesions, removal of foreign bodies, and repair of intestinal fistulae. She remained hospitalized for 12 days without significant complications and was discharged home. This case illustrates the potential for catastrophic abdominal complications to develop in a subacute fashion in patients with minimal or no initial symptoms. Pediatricians should have a low threshold to obtain plain radiographs in toddlers who present with inexplicable abdominal pain. Keywords: Magnet ingestion, Enteroenteric fistula, Phytobezoar, Small bowel obstruction